Managing Acute Esophageal Necrosis Secondary to Diabetic Ketoacidosis in a Rural Centre: A Case Report and Proposed Algorithm for Management - Annie Jiao Wang; Khang Duy Ricky Le; Shasha Haycock; Brendan Desmond; Matthew Shears (Clinical Case Reports)
ABSTRACT Acute esophageal necrosis (AEN) is a rare phenomenon, usually presenting with hematemesis or melena in patients who are already unwell with concurrent pathology. We present a case of AEN in an acutely unwell 82‐year‐old man who presented in diabetic ketoacidosis (DKA). He was successfully managed in our rural centre with remote guidance from a tertiary centre. We propose an evidence‐informed management algorithm to guide and assist clinicians caring for patients with AEN in resource‐limited settings. Initial management of AEN should prioritize resuscitation and correction of any underlying pathology, such as DKA. Early endoscopic assessment is required for the diagnosis of AEN and quantification of the extent of necrosis. Early repeat endoscopy (48–72 h) is recommended to assess healing and is useful in guiding ongoing management. In resource‐limited settings, early referral and transfer for patients with AEN is recommended in the absence of intensive care support, endoscopy, or limited blood products.